2018
DOI: 10.1108/itp-01-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of employers’ performance expectations for new IT graduates in individual and team work settings for software development

Abstract: Purpose In general, software development work environments involve many different tasks and have high demands on efficiency and quality of performance at both individual and team levels, which depend on the competencies of employees. However, the literature does not provide satisfactory evidence as for the characteristics and competencies of individuals. Especially, the employers’ expectations of new graduates have not been investigated in detail for different work environments. The purpose of this paper is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
(45 reference statements)
2
11
0
Order By: Relevance
“…These studies have revealed almost similar results in what the employers expect from graduates and will be vital since graduates at their current level itself can progress better The findings of the study show that employers' point of view, technical competencies for example competent in the software development processes and adaptable to new software development methods and approaches are an influence on both individual and teamwork settings. Comparable to this result, another study was conducted in turkey by Akman and Turhan (2018) found that new IT graduated employees should be competent in software development processes and software development methods that significantly related to individual and teamwork settings. But from this study, another result was found that software development solution is significant related with both settings which are individual and teamwork settings.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…These studies have revealed almost similar results in what the employers expect from graduates and will be vital since graduates at their current level itself can progress better The findings of the study show that employers' point of view, technical competencies for example competent in the software development processes and adaptable to new software development methods and approaches are an influence on both individual and teamwork settings. Comparable to this result, another study was conducted in turkey by Akman and Turhan (2018) found that new IT graduated employees should be competent in software development processes and software development methods that significantly related to individual and teamwork settings. But from this study, another result was found that software development solution is significant related with both settings which are individual and teamwork settings.…”
Section: Discussionmentioning
confidence: 82%
“…In this investigation, authors have used judgmental sampling technique where it identified as non-probability sampling technique, which depends based on the judgment of research team. The previous studies which similar to this study are frequently led by researchers had conveniently selected judgmental sampling technique (Akman & Turhan, 2018). Consequently, this technique of sampling was taken.…”
Section: Research Design and Methodologymentioning
confidence: 90%
See 2 more Smart Citations
“…In particular, ICT investment may be a labor-related expenditure (McGee, 2006), and intangible assets, such as internally developed SW produced by ICT staff, may be more than five times larger than the stock of hardware (HW) (Saunders, 2010). SW development involve many different tasks and has high demands on efficiency and quality of performance, which depend on the competencies of employees (Akman and Turhan, 2018).…”
Section: Introductionmentioning
confidence: 99%